مستدلّاتِ بیوع پراَسبابِ وُرودِ حدیث کے اثرات کا تحقیقی و اطلاقی جائزہ: A Research and Applied Evaluation of the Impact of the Reasons for the Revelation of Hadith on Commercial Inferences - Bhutta, Ghulam Yaseen; Buzdar, Prof. Dr. Abdul Qadir (Al-Amīr Research Journal for Islamic Studies, 2024)
Islamic Sharia encourages and commands individuals to perform certain actions in their practical lives while prohibiting others. After the Quran, the primary source of these commands and prohibitions in Sharia is the Prophetic Hadith. Since most Hadiths were revealed due to specific reasons, it is considered essential by Hadith scholars and jurists to take into account the reasons for the revelation of Hadith when deriving legal inferences. This is because a detailed understanding of whether rulings are absolute or conditional, general or specific, temporary or permanent can only be achieved by considering the reasons for their revelation. Therefore, scholars of jurisprudence have always considered the reasons for the revelation when deriving legal rulings from Hadith. Consequently, a significant portion of the jurisprudential evidence relies on these reasons. Furthermore, by considering the reasons for the revelation, many contemporary issues can also be resolved more easily. This study examines how the reasons for Hadith revelation influence the understanding of legal rulings, particularly in the context of commercial transactions. The research explores the application of these principles to contemporary commercial issues, highlighting the practical relevance of these causes in modern contexts. Keywords: Asbab al-Worood, Fiqh, Hadith, Commerce, Islamic Jurisprudence, Buyu’, Legal Rulings.